THE INFLUENCE OF SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION AT PT. ANDALAS CARGOTATAMA GLOBAL - BAMBANG SUTEJO; AFDHALINA . (JURNAL ILMIAH SIMANTEK, 2021)
This study aims to determine how much influence of service quality and price to customer satisfaction on PT. Global AndalasCargotama. The research methodology was used descriptive quantitative, unit analysis in this research was PT. GlobalAndalas Cargotama and its observation units were customers PT. Global Andalas Cargotama. Population in this researchwas customer at PT. Global Andalas Cargotama 1,260 people. The technique of determining the number of samples used inthis study was the slovin formula and amounted to 93 respondents. The research method used data collection techniquesthrough interviews, literature studies, and questionnaires conducted systematically based on research objectives. Themethod of analysis used to solve the problem and prove the hypothesis was by descriptive analysis, regression analysis.This analysis includes: validity and reliability, classical assumption test, multiple regression analysis, hypothesis testingthrough t and F test, and test of coefficient of determination (R2). From the analysis obtained regression analysis CustomerSatisfaction = 1.931 + 0.467 Service Quality + 0.226 Price + e. The result of determination coefficient test (R2) showed that58.1% variable of customer satisfaction is influenced by service quality and price variable, while the rest equal to 41.9%explained by the influence of other factors or variables outside of models such as advertising, distribution channels, andothers are not addressed in this study. F test results showed that Fcount> Ftable is 62.330 > 3.10 which means free variables(service quality and price) simultaneously affect the dependent variable (customer satisfaction). While the t test showed thatthe service quality variable has a positive and significant effect on customer satisfaction at PT. Global Andalas Cargotamawhere tcount 7,748 > ttable 1,66177 and price variable have positive and significant influence to customer satisfaction at PT.Global Andalas Cargotama where tcount 3.224 > ttable 1.